KONSTRUKSI SOSIAL MITOS KUTUKAN DEWI DANU DALAM MASYARAKAT MUNTI GUNUNG, TIANYAR BARAT, KARANGASEM - Setiawan, Gde Darma; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
Munti Gunung is an area known as the village of beggars, this is because beggars who are met in various cities in Bali always claim to be from Munti Gunung. This research was also conducted to analyze the social construction of the famous Dewi Danu curse myth in Munti Gunung and the impact caused by the myth of Dewi Danu's curse on the life of the Munti Gunung community. This study uses a qualitative approach with descriptive and explanative types. The theory used in this research is the social construction theory from Peter L. Berger with three dialectical stages, namely externalization, objectivation, and internalization. The impact of the myth of the curse of Dewi Danu are on the cultural poverty of Munti Gunung beggars, the construction of Padpad holy water spiritual tourism, the construction of a statue of Dewi Danu, and spiritual education through Pasraman Jiwan Mukti. Keywords: Poverty, Beggar, Curse, Goddess Danu